Edukasi Dietary Approaches Stop Hypertension (DASH) Sebagai Upaya Mengurangi Risiko Hipertensi - Saka Adhijaya; Dayuningsih Dayuningsih; Teti Oktianingsih (Abdimas Indonesian Journal, 2026)
Hipertensyon is one of the major non-communicable diseases and remains a leading cause of mortality in Indonesia. This community engagement program was implemented in RW 03, Harapan Mulya Subdistrict, with the objective of enhancing community knowledge and awareness regarding three primary topics: hypertension, the DASH (Dietary Approaches to Stop Hypertension) diet, and progressive muscle relaxation. The methods employed included a pre-test, educational intervention, and post-test. The educational session, attended by 16 participants, demonstrated an improvement in understanding as evidenced by the comparison of pre-test and post-test results. This intervention not only improved community health literacy but also strengthened collaboration among students, community health cadres, and local residents.